Field-induced mononuclear cobalt(ii) single-molecule magnet (SMM) based on a benzothiadiazole-ortho-vanillin ligand. Issue 12 (4th March 2022) - Plyuta, Nataliya; Petrusenko, Svitlana; Kokozay, Vladimir N.; Cauchy, Thomas; Lloret, Francesc; Julve, Miguel; Cano, Joan; Avarvari, Narcis
Abstract : A mononuclear octahedral cobalt(ii ) complex based on a unique benzothiadiazole- ortho -vanillin ligand shows slow relaxation of the magnetization under applied dc magnetic fields. Abstract : A unique π-conjugated benzothiadiazole- ortho -vanillin ligand (HL), characterized by single crystal X-ray diffraction and DFT calculations, has been prepared by condensation between 4-amino-benzothiadiazole (BTD) and ortho -vanillin. Its reaction with cobalt(ii ) acetate afforded the complex of formula [CoL2 ]·CH2 Cl2 (1 ), for which the coordination environment of the cobalt centre is a distorted octahedron and the ligand acts as a monoanionic tridentate NNO chelate in its phenolate form. Intermolecular π–π stacking interactions between the π-conjugated BTD units provide an antiferromagnetic coupling pathway, as indicated by the analysis of the dc magnetic measurements of a crystalline sample of the complex and supported by DFT type calculations. The static magnetic behaviour of 1 is analysed according to spin–orbit coupling and zero-field splitting models. Remarkably, the complex exhibits slow relaxation of the magnetization under dc applied magnetic fields being thus a new example of field-induced mononuclear single-molecule magnet (SMM).